Kinerja Protocol Location Aided Routing (LAR) terhadap serangan Wormhole pada Jaringan Mobile Ad-Hoc Network (MANET) - Hasan Sabiq; Primantara Hari Trisnawan; Reza Andri Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mobile ad-hoc network (MANET) is a network that can function without a fixed infrastructure. In MANET, the communication process is managed using a mechanism called a routing protocol. In this case, a problem arises that generally can occur in MANET, namely network security problems. Wormhole itself is a network attack that cannot be carried out by one node, because basically a wormhole attack forms a tunnel that connects one wormhole node with other wormhole nodes. Therefore, this study evaluates the impact of wormhole attacks on the MANET network using the Location Aided Routing (LAR) routing protocol. From the results of the tests carried out, the effect of increasing the number of nodes in the network before the wormhole attack occurred to get the best value from the packet delivery ratio parameter of 97.13% for a variation of 40 nodes. For the average end to end delay parameter, the best value is obtained at a variation of 20 nodes with a value of 57.06ms. And the best value of the routine overhead parameter is obtained at a variation of 40 nodes with a value of 0.73. While in the scheme after the wormhole attack, the value of the packet delivery ratio parameter increased significantly, achieved at a variation of 30 nodes with a value of 99.92%. For the average end to end delay parameter, the best value is obtained at a variation of 30 nodes with a value of 41.62ms. And for the routine overhead parameter, the best value is obtained at a variation of 30 nodes with a value of 0.18..